The Isotherm Adsorption of Cu2+ Ions in Aquoeus Solutions by Cross-Linked Chitosan-Cellulose Membrane Composite - Santoso, Eko; Yuwono, Hendro; Ratnawati, Yohana (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2007)
The isotherm adsorptions of Cu2+ ions in aqueous solutions by cross-linked chitosan-cellulose composite membranes were investigated. The equilibrium isotherm adsorption studies were done in a batch system. The composite membranes have been prepared by coating 1 %, 2%, and 3 % (m/v) chitosan solution containing 1 % (m/v) acetic acid onto the grade 4 whatman paper filter and cross-linked by glutaraldehide. The effects of polyethylene glycol additive as a porogen agent of the composite membranes on the adsorption abilities were investigated also. The linear regression method was used to fit the adsorption data with the Langmuir model dan the Freundlich model. The fitting results show that the adsorption data more fit to the Langmuir model with the correlation coefficient value R2 higher than 0.97. The fitting of adsorption data to the Freundlich model result the correlation coefficient value R2 between 0.84–0.88. Furthermore, the Langmuir model was used to calculate the maximum adsorption capacity per surface area unit of the composite membrane (Qm) and the maximum adsorption capacity per weight unit of the composite membrane (Km). The results show that Qm increase with the increasing of chitosan concentration. The additions of PEG have increased Qm too. But 5% (m/v) PEG has increased Qm more higher than 10% (m/v) PEG. However, both the increasing of chitosan and the addition of PEG have decreased Km.